Lei de alienação parental (Lei n° 12.318/2010): análise da aplicabilidade e efetividade no processo - Jesus, Sheila Machado de (2016)
At the discourse among Psychology and Law extracts the value of understanding the complex phenomenon of parental alienation, observed in family disputes, with injustifiable resistance, whether in the failure of the relationship, by lack of love, affection for the child, selfish or narcissistic reasons, or any other reason, depending on the emotional structure of those involved and the presence of personality disorders, triggering real battles, remorselessly, which leads to compulsive set to the detriment that is not only of the child's personality development, but also the family relationship and the effectiveness of judicial provisionses. The purpose of this research was to evaluate the applicability and effectiveness of Parental Alienation Law considering the increased occurrences sented to the courts every day. As a result of impossibility in consulting the documents of process, shield by judicial secret of the mantle, it undertook a descriptive statistical analysis (n=50) of case law of the Court of Justice of Paraná State, which were randomly selected, by an exclusion criterion, picked those jugdment given in the years 2015 and 2016, using a tally sheet and SPSS Statistics software as an instrument. The results showed the attempt to trivializing the phenomenon and manipulation of the judiciary by those involved, using impediments and unjustified disqualification campaigns, false accusations of criminal wrongdoing by the irresponsible and indiscriminate use of Law 12.318/2010 for satisfaction of own interests, on the detriment of physical and psychological integrity of children and adolescents.